Currency board arrangements : issues and experiences - Balino, Tomas J.T....[et al] (IMF WashingtonUS, 1997)
Reviews the costs and benefits of currency board arrangements (CBAs) and discusses the main conditions for entry. Discusses the trade-off between flexibility and credibility in CBAs and whether they should best be viewed as transitional arrangements.